Impact and policy supporting Thailand innovation driven enterprise: orchestrating university innovation and entrepreneurship ecosystem with public and private stakeholders - Natcha Thawesaengskulthai; Awirut Chatmarathong; Jarotwan Koiwanit (My University, 2024)
Abstract This research paper aims to investigate the impediments faced by innovation-driven enterprises in Thailand and to explore the current measures, policies, and mechanisms related to innovation-driven enterprises (IDEs)’ development both domestically and internationally. The study encompasses a comprehensive approach, including an analysis of an innovation entrepreneur database comprising 320 investors and 883 IDEs. Moreover, semi-structure in-depth interviews were conducted with three investors, twenty-two IDEs’ founders, eight executives, and experts from various sectors, including government, university incubators, and the private sector in Thailand. Through this multifaceted investigation, this paper sheds light on the key factors that hinder the success of IDEs in Thailand, which primarily revolve around the quality of entrepreneurs (Team), Product and Market Fit, and Support. These factors collectively impact the depth of knowledge, business incubation, acceleration programs, and the effectiveness of laws, measures, and policies in supporting innovation capability development within IDEs. In addition, this paper presents a framework for Thailand’s IDEs hub, facilitating the connection between the university's innovation and entrepreneurship ecosystem with public and private stakeholders. This framework serves as a mechanism to address the identified hindrances and foster a conducive environment for IDEs development. To address the obstacles, this paper proposes three crucial strategies, namely, (1) talent management, (2) ease of doing scaleup, and (3) availability of funding. These strategies are envisioned to counteract the identified challenges and can be effectively implemented through an operating model and practical working procedures tailored to suit the specific context of Thailand.
Keywords: Private enterprise; Innovation Management; Open Innovation; Innovation Policy and R&D